Comparative Usability Analysis of University Department Websites: A Case Study of Industrial and Chemical Engineering Programs - Kirana, Intania Widyantari; Nugraha, Isna; Novasani, Raditya Jarwenda (LPPM Universitas Dian Nuswantoro, 2025)
This study's goal was to compare the usability of the websites for the Industrial Engineering and Chemical Engineering departments at a university. Since these sites are critical for new students seeking information, a user-friendly interface is essential for efficient and accurate information retrieval. To conduct the study, a user performance test was administered to 40 new students, all with less than a year of study. They were asked to complete three specific tasks: downloading a form, finding a